GAMBARAN RESPON PSIKOLOGIS SAAT MENARCHE PADA SISWI KELAS 4-6 SD KHADIJAH SURABAYA - R. Khairiyatul Afiyah (Universitas Nahdlatul Ulama Surabaya, 2016)
Menarche is a physiological condition which definitely happens to each normal woman which should not be worried about. However, many adolescents feel ashamed and anxious when menarche comes. Therefore, the purpose of this study was to know the description of the attitude of sixth-grade adolescents when having menarche in SD Khadijah (State Elementary School) Surabaya. Design of this study was descriptive. The population were all students four until sixth-grade when having menarche in the SD Khadijah Surabaya, totally 50 respondents. Number of samples were 50 respondents taken by suing non-probabilit sampling, in which total sampling technique was used in this study. The instrument used to collect the data was a questionnaire. Moreover, the data were processed by editing, coding, scoring, and tabulating, then were analyzed descriptively in the frequency distribution table. The result of study showed that among 50 respondents, most of them (66.7%) had negative attitude, whereas nearly half of them (33,7%) had positive attitude on menarche. The conclusion of study was that most of the female adolescents had negative attitude on menarche. therefore as health care worker provide consuling to students on menarche, so that they have the correct understanding about menarche.